2012
DOI: 10.1007/s10237-012-0434-3
|View full text |Cite
|
Sign up to set email alerts
|

An experimental and computational investigation of the post-yield behaviour of trabecular bone during vertebral device subsidence

Abstract: PublisherSpringer-Verlag AbstractInterbody fusion device subsidence has been reported clinically. An enhanced understanding of the mechanical behaviour of the surrounding bone would allow for accurate predictions of vertebral subsidence. The multiaxial inelastic behaviour of trabecular bone is investigated at a microscale and macroscale level. The post-yield behaviour of trabecular bone under hydrostatic and confined compression is investigated using micro-computed tomography derived microstructural models, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 62 publications
2
25
0
Order By: Relevance
“…Highly localised pressures are computed near the bone-implant interface for the CFI plasticity formulation which leads to high levels of localised plastic yielding directly at the interface; hence, lower stresses and pressures are computed further into the trabecular material. Although the present study focuses on PU, a synthetic trabecular analogue material, the ability of a CFI plasticity formulation to capture the multiaxial pressure dependent plasticity of natural trabecular bone has previously been observed [14,16]. Highly localised peri-prosthetic plasticity has also been observed experimentally during vertebral fusion device subsidence [16].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Highly localised pressures are computed near the bone-implant interface for the CFI plasticity formulation which leads to high levels of localised plastic yielding directly at the interface; hence, lower stresses and pressures are computed further into the trabecular material. Although the present study focuses on PU, a synthetic trabecular analogue material, the ability of a CFI plasticity formulation to capture the multiaxial pressure dependent plasticity of natural trabecular bone has previously been observed [14,16]. Highly localised peri-prosthetic plasticity has also been observed experimentally during vertebral fusion device subsidence [16].…”
Section: Discussionmentioning
confidence: 99%
“…With ever increasing computational power, microstructural based models of macroscale bone-implant applications that include complex non-linear material behaviour, contact conditions and finite deformation may be feasible in the near future. As demonstrated by , the explicit modelling of the trabecular bone microstructure will still require plastic yielding or damage at a material level in order to provide realistic macroscopic behaviour [16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[9][10][11] Most studies that evaluated OMIs using FEA have assessed their results using equivalent stress. [2][3][4][5][6][7][8] Recent studies 26 showed that von Mises stress does not reliably predict the yielding behavior of bone and that the principal strain criterion correctly identified the risk of failure. 13,27 Consistent with these studies we found equivalent stress to be significantly correlated to stability only in zone 2, and it explained only a small amount of the variation in stability observed in the sample (R 2 5 0.1706).…”
Section: Discussionmentioning
confidence: 99%